Building Without a Plan: The career experiences of Australian strength and conditioning coaches - Dawson, A. J.; Leonard, Z. M.; Wehner, K. A.; Gastin, P. B. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this investigation was to explore the career experiences of Australian strength and conditioning coaches. Six Australian strength and conditioning coaches (mean age = 33.7 years, SD = 6.0 years) with a mean of 10.4 (SD = 4.9) years experience working with elite Olympic and professional athletes were interviewed about their experiences of career development. Each interview was transcribed verbatim and analyzed to produce key themes and subthemes relating to (a) work environments, (b) sport management practice, (c) career development processes, and (d) career building strategies. The work environments of Australian strength and conditioning coaches were found to be poor because of long working hours and irregular human resource policy and management practices of sport organizations. Because of the volatile and unpredictable nature of their working conditions, the coaches interviewed have only a short-term view of their career creating considerable stress in their lives. The coaches interviewed found it difficult to develop their careers because their only options were self-supported and self-funded professional development activities. The coaches in this study believed that more needed to be done at a policy and management level by sport organizations and their professional body to enhance the career development of strength and conditioning coaches because they play a key role in both athlete and sport organization performance. These results may help sport organizations develop policies and management practices that enhance the careers of strength and conditioning coaches and will have important practical implications for the education and development of sport professionals.